Dataset of geoelectrical properties for samples obtained at the Higashi-Aogashima Knoll Caldera hydrothermal field, JapanOpen Science Framework - Yusuke Ohta; Tatsuo Nozaki; Takafumi Kasaya (Data in Brief)
This dataset contains fundamental measurements and analyses of rock samples collected from seafloor hydrothermal fields, with a focus on their physical and electrical properties. The dataset includes porosity and particle density measurements obtained via the buoyancy method and complex impedance data acquired through potentiostat-based electrochemical impedance spectroscopy with frequency sweeps. Additionally, impedance data provides Cole-Cole fitting analyses and corresponding graphical representations, which are essential for understanding the polarization characteristics of rock samples. Rocks in seafloor hydrothermal field often exhibit unique properties that are distinct from those of terrestrial rock physics models, necessitating specialized datasets for the accurate interpretation of seafloor geophysical and electromagnetic exploration. This dataset aims to bridge this gap by offering comprehensive data to aid in the interpretation of resistivity structures and improve rock physics models for seafloor hydrothermal systems. The data and figures provided herein are expected to facilitate advancements in the study of seafloor hydrothermal deposits and their resource potential.